2015
DOI: 10.1890/14-1989.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of weather on long‐term patterns of plant richness and diversity vary with location and management

Abstract: Better understanding the influence of precipitation and temperature on plant assemblages is needed to predict the effects of climate change. Many studies have examined the relationship between plant productivity and weather (primarily precipitation), but few have directly assessed the relationship between plant richness or diversity and weather despite their increased use as metrics of ecosystem condition. We focus on the grasslands of central North America, which are characterized by high temporal climatic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 67 publications
(80 reference statements)
0
23
0
Order By: Relevance
“…However, there was a significant negative relationship between altitude and mean annual temperature (Fig. In central North America, Jonas et al (2015) found that temperature acted as an important regulator on variations of species richness and diversity. 9d); therefore, our analysis showed that temperature dependence on altitude was comparatively higher than precipitation on the northern slope.…”
Section: Factors Controlling Aboveground Biomass and Species Richnessmentioning
confidence: 99%
“…However, there was a significant negative relationship between altitude and mean annual temperature (Fig. In central North America, Jonas et al (2015) found that temperature acted as an important regulator on variations of species richness and diversity. 9d); therefore, our analysis showed that temperature dependence on altitude was comparatively higher than precipitation on the northern slope.…”
Section: Factors Controlling Aboveground Biomass and Species Richnessmentioning
confidence: 99%
“…Thus, water content in soil poses a major selective pressure in shaping soil microbial communities. Recent studies have documented that soil relative humidity is positively correlated with the richness of the soil microbiota (Lau and Lennon, 2012;Blazewicz et al, 2014;Jonas et al, 2015;Taketani et al, 2017). Rhizosphere bacterial communities from semi-arid ecosystems show a drastic increase in bacterial abundance during the wet season compared with the dry season.…”
Section: Effect Of Water On Rhizosphere Microbesmentioning
confidence: 99%
“…Land plants obtain water mainly from soil, whereas microbes that live in or on land plants gain water from the plant and/ or water vapor from the atmosphere. Water availability is known to have a great impact on plant diversity and microbial community structure (Lau and Lennon, 2012;Blazewicz et al, 2014;Jonas et al, 2015;Taketani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that vegetation composition was largely driven by management alternatives may be more a reflection of the way that climate was incorporated into this model than actual climate/ vegetation relationships, and considerably more work needs to be done to better evaluate their relative contributions (e.g., Haferkamp et al 1993, Collins et al 2012, Koerner and Collins 2014, Jonas et al 2015. Regardless of the relative influence of climate and management, model results pointed to a tradeoff between the proportion of desired vegetation (e.g., WW/needle and thread) versus undesired vegetation (e.g., cool exotic grass) and biomass.…”
Section: Model Resultsmentioning
confidence: 99%
“…, Koerner and Collins , Jonas et al. ). Regardless of the relative influence of climate and management, model results pointed to a tradeoff between the proportion of desired vegetation (e.g., WW/needle and thread) versus undesired vegetation (e.g., cool exotic grass) and biomass.…”
Section: Discussionmentioning
confidence: 99%